Paramedics knowledge about providing paediatric advanced medical resuscitation procedures - Rafał Czyż; Mateusz Zawłodzki; Izabela Czyż (Kazimierz Wielki University, 2017)
Child in emergency state requires treating in the fast and precise way. It is possible only in the situation when medical staff is having up-to-date knowledge and the ability in providing aid to such a patient's. The aim of this study was to evaluate the knowledge level about providing paediatric advanced medical resuscitation procedures by paramedics working in National Emergency Medicine System. In examination took part 186 paramedics working in emergency ambulance services and in hospital emergency departments. Average age of the group amounted to 29.1 ± 5.4 of years. The anonymous and author's questionnaire form made up of 22 questions concerning socjodemographic data, as well as specialist medical knowledge. The average test result of knowledge level about paediatric advanced medical resuscitation procedures from entire group amounted 8.9 ± 2.9 points. Paramedics from ambulance services achieved the better average outcome than emergency departments rescuers (8.9 ± 3.0 vs 8.8 ± 2.8). Only 44% examined rescuers participated in child resuscitation course. Paramedics most often assessed their knowledge in the examined scope on the average level (55%). Less than ¾ of rescuers knows formula being used to convert the child age into approximate body weight. Alarming is a fact that only 76% examined is able to give right dose of adrenaline for child with weight of 10 kg. 66% of paramedics would carry out defibrillation to child with weight of 18 kg with correct energy. Knowledge in the scope of advanced medical resuscitation procedures to the paediatric patient by paramedics is insufficient. It is essential to increase amount of children resuscitation trainings amongst medical staff.